Precipitate-dislocation interaction mediated Portevin-Le Chatelier-like effect in a beta-stabilized Ti-Mo-Nb-Al alloy. (November 2016) - Choudhuri, Deep; Mantri, Srinivas Aditya; Alam, Talukder; Banerjee, Srikumar; Banerjee, Rajarshi
Abstract: Portevin-Le Chatelier (PLC)-like effect was observed in a commercial alloy based on Ti-Mo-Nb-Al, which exhibited serrations in its tensile stress-strain response within a temperature-strain rate window. The serrations manifested as repeated load-drop and rise, and were rationalized on the basis of sudden plastic flow along the "soft" ω precipitate free micro-slip-bands created by the passage of leading dislocations in the parent β matrix. Subsequently, dynamic precipitation of the α phase occurred within the ω-free micro-slip-bands. These results demonstrate that the PLC-like effect can be manifested via precipitate-dislocation interactions, and is not limited to the traditionally accepted solute-dislocation interactions. Graphical abstract: